Coordinated Overcurrent Relay Development with Arduino and ACS712 - Luis Santos, José; Miguel, Reyes Carlos; Isabel Mendoza, Antonio; Garcia, Juan Alvarez (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This study presents the design and evaluation of an overcurrent relay system using Arduino Uno, ACS712 current sensors, and electromagnetic relays. Conducted at the University of Negros Occidental–Recoletos, Philippines, from March 2023, the research focuses on developing a relay with accurate trip times and reliable performance. The designed relay features multiple characteristics including Standard Inverse, Very Inverse, and Extremely Inverse, with time delays ranging from 20 ms to 100 ms and time multiplier settings from 0.1 to 0.23. Testing results showed that the Extremely Inverse characteristic achieved the fastest trip time of 0.11 seconds at 9.3 A, while the Normal Inverse characteristic had a trip time of 1.04 seconds at 1.7 A. The relay's error margins were well within the 5% tolerance limit set by IEC 60255 standards, with errors ranging from 0.027 to 0.028. Effective coordination was achieved by adjusting the Time Multiplier Setting (TMS) values to ensure fault isolation without disrupting other system components. The results confirm that the relay design is both accurate and reliable, suitable for practical implementation in electrical protection systems. Future work could involve integrating additional functionalities and testing under diverse environmental conditions.